Penyuluhan Tentang Peran Penting Marketplace dalam Memasarkan Produk di Desa Bandung Kecamatan Banjar Kabupaten Pandeglang Banten, Indonesia - Hawwa Nasywa Aqillah; Mohamad Satrio Agung; Roy Martin; Agus Sukirno (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses counseling on the important role of marketplace platforms in helping product marketing in Bandung Village, Banjar District, Pandeglang Regency, Banten, Indonesia. The purpose of this counseling is to increase the understanding of the village community on how to effectively use the marketplace to expand market reach, increase sales, and support the local economy. With the development of technology, the use of marketplaces is a strategic solution in facing increasingly fierce market competition. This counseling provides practical guidance to local business actors on the steps to start an online business, digital marketing strategies, and tips for successfully selling on marketplace platforms.